Public sphere contestation: configuration of political Islam in contemporary Indonesia - Zuly Qodir (IAIN Salatiga, 2011)
Argument in this paper draws upon Habermasian understanding of the distinctionbetween private and public sphere. Public sphere is understood as openspace that various social and cultural forces seek to define and occupy by ways ofrational interests and public reason. Such attempts take place on daily basis andtaken by groups of different backgrounds and interests. Private sphere, in contrast,is conceived of as having domestic or individual characteristics and, moreor less, non-political. It is within this framework that the continuing presence ofmultiple variants of political Islam in Indonesia has been a manifestation of contestationover public sphere. Diverse variants of Indonesian political Islam revealthe difference between actors and issues in the dynamics of their contention.However, evidence makes clear that variants of both political and popular Islamhave been more dominant than other Islamic variants such progressive and neotraditionalistIslam. This study argues that mode of Islamic articulations in Indonesiais now more diverse as the it has developed not only in the articulatoryforms of modernist, revivalist and traditionalist but also progressive, neo-traditionalistand popular Islam.Tulisan ini didasarkan pada kerangka ruang publik Jurgen Hubermas yangmembedakan ruang privat dan ruang politik (publik). Ruang publik merupakanruang yang terbuka untuk diperebutkan oleh siapa pun dan kapan pun. Sementararuang privat merupakan ruang yang bersifat domestic (individual) tidak berdimensipolitik secara dominan. Dalam persepktif semacam itu, hadirnya varian-varianIslam Indonesia merupakan bentuk kontestasi atas ruang publik yang terbukauntuk siapapun. Dari varian-varian Islam Indonesia, ada perbedaan aktor danisu yang dikembangkan dalam kontestasi publik. Hanya saja kontestasi varianIslam politik dan popular mendapatkan ruang lebih dominan ketimbang varianIslam lain seperti progresif atau neo-tradisionalisme. Kajian ini menunjukkanbahwa Islam Indonesia tengah mengalami perkembangan format artikulasi yangsangat beragam. Islam Indonesia tidak hanya berkembang dalam formatmodernis, revivalis, tradisionalisme, tetapi sekaligus progresif, neo-tradisionalisdan popular Islam.